JIBE 2017
DOI: 10.51240/jibe.2017.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management and Financial Crisis: Evidence from India

Abstract: This paper attempts to examine the earnings management behavior of Indian firms during the global financial crisis in 2008 and compare with the period before and after. It uses the financial data of S&P CNX 500 companies for the period of 2007-2012. GICS, the best industry classification system among competing alternatives, has been used for computing discretionary accruals (DA). The study finds a high level of earnings management in firms during the pre-crisis period, a significant decrease during the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 0 publications
2
30
0
2
Order By: Relevance
“…Çalışmada 2008 finansal krizinde şirketlerin kazanç yönetimi eğilimlerinin arttığı tespit edilmiştir. Kumar ve Vij (2017) çalışmalarında 2008krizi öncesi (2007-2008), kriz sürecinde (2009 ve kriz sonrasında (2011-2012) gerçekleşen kar yönetimi uygulamaları karşılaştırmış, kriz sürecinde şirketlerin kar yönetimi uygulamalarının azaldığı, sonrasında ise kar yönetimi uygulamalarının arttığı tespit edilmiştir.…”
Section: Li̇teratür Taramasi Ve Araştirma Hi̇potezi̇unclassified
See 1 more Smart Citation
“…Çalışmada 2008 finansal krizinde şirketlerin kazanç yönetimi eğilimlerinin arttığı tespit edilmiştir. Kumar ve Vij (2017) çalışmalarında 2008krizi öncesi (2007-2008), kriz sürecinde (2009 ve kriz sonrasında (2011-2012) gerçekleşen kar yönetimi uygulamaları karşılaştırmış, kriz sürecinde şirketlerin kar yönetimi uygulamalarının azaldığı, sonrasında ise kar yönetimi uygulamalarının arttığı tespit edilmiştir.…”
Section: Li̇teratür Taramasi Ve Araştirma Hi̇potezi̇unclassified
“…Nitekim Covid-19 kriziyle birlikte nakit dengesi, mali yapısı bozulan ve finansal performansında ani ve hızlı düşüşler meydana gelen şirketlerin, salgının mali tablolar üzerindeki olumsuz etkilerini giderebilmek, sürdürülebilir performans göstergelerine sahip olabilmeli ve finansal analistlerin (yatırımcıların) kar beklentilerini karşılayabilmek adına raporlanan karı artırma eğiliminde olabilmeleri muhtemeldir (Xiao ve Xi, 2021;Choi vd., 2011). Diğer taraftan Covid-19 gibi kriz süreçleri, işletmeleri kar yönetimi konusunda teşvik etmektedir (Azizah, 2021;Kumar ve Vij, 2017). Bu doğrultuda Borsa İstanbul'da kote olmuş şirketlerin Covid-19 öncesi (2019) döneme göre, Covid-19 krizi (2020) sürecinde karı artırmaya yönelik kar yönetimi uygulamalarını artırıp artırmadığının tespiti önem arz etmektedir.…”
Section: Introductionunclassified
“…And the effects of female participation on boards and executives on real earnings management are also different in bullish and bearish periods. When firms are in recession conditions, managers may increase revenue and avoid losses to manipulate earnings (Habib et al, 2013), but Kumar and Vij (2017) reported that the extent of earnings management is relatively low during the crisis period than bullish period. When firms are in the bull period, the level of earnings manipulation is relatively high (Kumar & Vij, 2017), but Cimini (2015) argued that the extent of earnings management would decline in this period.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Thus, it is vital to examine earnings management practices during the global financial crisis in Jordanian nonfinancial listed firms, as there is a little known about financial crisis and its relation to earnings management in the context of small emerging economies, such as Jordan. Most studies focus on the U.S., Europe, Asia and other developed markets, in addition, studies on the link between financial crisis and earnings management reported mixed results (see for example, Bartram & Bondar, 2009;Mollik et al, 2013;Filip & Raffournier, 2014;Cimini, 2015;Xu & Ji, 2016;Costa, 2016 andKumar &Vij, 2017). This paper sets out to examine the behavior of firm's earnings management during the global financial crisis (2008)(2009) in the context of nonfinancial firms listed in emerging markets, taking ASE as a representative of these markets (Note 1).…”
Section: Institutional Environment and Corporate Ownership In Jordanmentioning
confidence: 99%
“…Studies from developing markets have examined earnings management during the financial crisis period. For example, Kumar and Vij (2017) study the attitude of earnings management during the global financial crisis ( 2008) and compare it with period before and after-crisis for a sample of 356 Indian listed firms selected from S &P 500 index for the period of 2007-2012. As for their methodology; they used an OLS regression model to examine earnings management, Furthermore, they classify firms into two groups: the first group is firms with positive discretionary accruals and the second one is firms with negative discretionary accruals.…”
Section: Related Literaturementioning
confidence: 99%